2021
DOI: 10.1002/jqs.3381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social and climatic factors on building activity in the Czech lands between 1450 and 1950: a dendrochronological analysis

Abstract: The development of settlement and building activity is the result of socioeconomic, political and demographic changes in the past. However, accurate information on temporal variation in building activity is rather limited. Dendrochronological databases containing dated historical wooden constructions provide an important resource. We used 6514 tree-felling dates to reconstruct building activity in the Czech lands for the period 1450-1950. Comparing felling dates with historical events demonstrated that buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The most important difference is arguably a more stepwise, and slightly later, recovery in building activity following the Late Medieval Crisis. Another noteworthy feature is an earlier onset of the "Crisis of the Seventeenth Century" (Hobsbawm, 1954;Parker, 2013), also evident in the recent felling-date-based study for Czechia by Kolář et al (2022).…”
Section: Felling Dates As a Historic Source Materialsmentioning
confidence: 82%
See 2 more Smart Citations
“…The most important difference is arguably a more stepwise, and slightly later, recovery in building activity following the Late Medieval Crisis. Another noteworthy feature is an earlier onset of the "Crisis of the Seventeenth Century" (Hobsbawm, 1954;Parker, 2013), also evident in the recent felling-date-based study for Czechia by Kolář et al (2022).…”
Section: Felling Dates As a Historic Source Materialsmentioning
confidence: 82%
“…Felling dates could be compared with grain prices on regional scales where the grain prices are identified through hierarchical cluster analysis to strongly co-vary. Future studies could strive to compare the association between the number of felling dates and plague outbreaks on local to regional scales [as done for Ireland by Mallory and Baillie (1988) and Baillie (2006), and for Czechia by Kolář et al (2022)]. Ljungqvist et al (2018) found that the number of plague outbreaks, at an aggregated scale, showed an even stronger association with the number of felling dates than grain prices.…”
Section: Prospects For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Czech Lands, depopulation is estimated to have been around 30 %, although the accuracy of this figure is questionable due to unreliable population estimates before the TYW (Maur, 1987;Fialová et al, 1996). However, a significant decrease in population is evident in the region through a substantial decline in building activity, which dropped by more than 30 % during the TYW compared to the previous 30 years (Kolář et al, 2022).…”
Section: Human Impacts and Responsesmentioning
confidence: 98%
“…Further issues arise in the integration of historical climatology and paleoclimatology: that is, reconstructions based on archives of societies and those based on archives of nature. High‐resolution paleoclimate proxies such as tree‐ring width and density promise valuable insights into climate variability and impacts on human historical scales, independently or alongside information from written records and artifacts (e.g., Kolář et al, 2022; Ljungqvist et al, 2019). Recent studies have engaged in systematic comparisons of historical records with tree ring‐based reconstructions to identify strengths, weaknesses, and patterns in results.…”
Section: Emerging Challenges (1): Integrating Evidencementioning
confidence: 99%